1993
DOI: 10.1111/j.1460-9592.1993.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled analgesia in children. A comparison of two infusion techniques

Abstract: The effectiveness of patient-controlled intravenous morphine with and without a supplementary fixed rate infusion was studied in 40 children after orthopaedic surgery and 40 children after abdominal surgery. The use of a background infusion after orthopaedic surgery, where the majority of children received intra-operative regional blockade, resulted in a higher total dose of morphine (P < 0.05) without evidence of improved analgesia, compared to PCA alone. Children receiving a background infusion after abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…Of these, independent review yielded 7 eligible randomized trials (338 patients) for inclusion (Table 1). 8,9,[11][12][13][14][15] Figure 1 illustrates the results of our literature search. Patients' ages ranged from 5 to 20 years, and all Twenty-three subjects were assigned to a third group, IM morphine, which was not included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, independent review yielded 7 eligible randomized trials (338 patients) for inclusion (Table 1). 8,9,[11][12][13][14][15] Figure 1 illustrates the results of our literature search. Patients' ages ranged from 5 to 20 years, and all Twenty-three subjects were assigned to a third group, IM morphine, which was not included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The second study reported no difference in the proportion of patients who experienced none, mild, or moderate/severe pain with the addition of a highdose background infusion of morphine at 20 μg/kg/h. 14 …”
Section: Patient-reported Pain Scoresmentioning
confidence: 97%
See 3 more Smart Citations